2017
DOI: 10.1182/bloodadvances.2017005900
|View full text |Cite
|
Sign up to set email alerts
|

Clonality of HTLV-1–infected T cells as a risk indicator for development and progression of adult T-cell leukemia

Abstract: Key Points• Oligo-or monoclonal expansion of HTLV-1-infected T cells in asymptomatic carriers predicts the onset of ATL.• Progression to acute type from indolent ATL was observed only in cases with monoclonal expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
(37 reference statements)
1
28
0
Order By: Relevance
“…We then run the simulations on other available tools for IS identification such as VISPA [ 22 ], Mavric [ 16 ], SeqMap [ 14 ] and QuickMap [ 15 ] and we evaluated their performances (Table 1 , Additional file 2 ). VISPA2 showed a precision and recall of 1.0 and 0.97 respectively, a clear improvement with respect to VISPA [ 6 ], Mavric [ 9 ], and SeqMap [ 7 ] (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…We then run the simulations on other available tools for IS identification such as VISPA [ 22 ], Mavric [ 16 ], SeqMap [ 14 ] and QuickMap [ 15 ] and we evaluated their performances (Table 1 , Additional file 2 ). VISPA2 showed a precision and recall of 1.0 and 0.97 respectively, a clear improvement with respect to VISPA [ 6 ], Mavric [ 9 ], and SeqMap [ 7 ] (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The clonality analysis of HTLV-1-infected T cells was also performed by high-throughput sequencing based mapping of proviral integration sites (15). To designate the virus integration site, the sequences spanning the viral and human genomes were identified and their junction points were extracted by as the soft-clipped read using the perl script and then validated by using Blastn, version 2.6.0+.…”
Section: Methodsmentioning
confidence: 99%
“…We thus asked whether patients with HAM/TSP are under increased risk of developing ATLL. Previous prospective studies demonstrated that peripheral blood HTLV-1 proviral load (PVL) at or more than 4% and clonal expansion of HTLV-1-infected cells reflect a high risk of ATLL transformation in HTLV-1 carriers (14,15). Although patients with HAM/TSP have increased HTLV-1 PVL compared with that of HTLV-1 carriers (16), whether or not they are at increased risk of developing ATLL has never been investigated.…”
mentioning
confidence: 99%
“…Longitudinal monitoring of clonality among infected cells using HTLV-1 integration sites indicates that clonal expansion of infected cells occurs from the early stages of infection, even when individuals are still healthy and are diagnosed as asymptomatic carriers. Individuals with a largely expanded infected clone have a high risk of ATL development [37] , [38] . However, it is not clear whether the expanded cell populations are homogeneous or heterogeneous at a mutation level.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the clonality pattern and the number of clones based on the provirus integration sites [34] indicates that the absolute abundance of infected and leukemic clones is a determining factor for ATL development [35] , [36] . High-throughput longitudinal analysis indicates that infected individuals with small clones and polyclonal patterns remain healthy over time, whereas those with large clones having an oligo- or monoclonal pattern develop ATL [37] , [38] . Also, recently a study on multi-organ clonality analysis in Simian T-Lymphotropic Virus type-1 associated leukemia- a simian counterpart of ATL- reported a complex clonality pattern in this disease [39] .…”
Section: Introductionmentioning
confidence: 99%